Human aspects of IT for the aged population. design for aging : second International Conference, ITAP 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016. Proceedings /: design for aging : second International Conference, ITAP 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016. Proceedings. Part I : ([2016]) - Unknown
No abstract available